Desired Leader Profile in Educational Sector in Iceland - Urboniene, Lolita, 1966- (2017)
The aim of this master’s thesis was to develop an understanding about the specifics of leadership in the educational sector in Iceland from the followers’ point of view, particularly regarding the desired leader behaviour profile. Quantitative research method was used, as it allows to reach a larger number of employees working in the educational sector, namely in kindergarten, compulsory and secondary schools in Iceland. For answering the research question and describing the profile of the desired leader in the educational sector in Iceland, the questionnaire comprised of Leader Behaviour Description Questionnaire XII and Values Survey Module 2008 was used. Sample data was processed using SPSS program. The results indicated that most desired leader behaviour in the educational sector in Iceland were Demand Reconciliation, Integration, Representation and Consideration. The societal culture of the educational sector in Iceland were described using the VSM 08 seven-dimensional model. The results indicate that highest scoring dimensions were Individualism vs. Collectivism (IDV), Indulgence vs. Restrain and Power Distance (PDI) dimensions. An attempt was made to relate societal cultural dimensions to the desired leader preferences, for checking if societal cultural context in the educational sector in Iceland could predict leader behaviour preferences. Analysis indicated some connections, but they were weak and had low predictive value. Influence of sociodemographic factors on follower´s preferences was analysed, and the results indicated a weak correlation between respondents‘ age and their cultural preferences. However, due to low number of participants of the particular age group, this implication should be considered carefully. The research was dedicated to educational sector leaders in Iceland and practitioners in the field of management. The thesis provides suggestions for further research. Viðskiptafræðideild hefur samþykkt lokaðan aðgang að þessari ritgerð í þrjú ár.